Revisiting the Concept of Nusyūz: A Recontextualised Understanding in Contemporary Marital Life - Hamza Abed Al-Karim Hammad (PT. Islamic Research Publiser, 2025)
The meaning of the concept of Nusyúz in society often differs from its true meaning in Islamic law. Many people still assume that Nusyúz can only be committed by a wife, while Islamic teachings actually provide a more balanced perspective. This field study was conducted in Jordan to explore how the concept of Nusyúz is understood and practised among Muslim families in contemporary society. The research aims to uncover both the factual realities and the doctrinal meanings of Nusyúz as interpreted within Jordanian social and religious contexts. Using a qualitative approach, data were collected through interviews, observations, and document analysis, while triangulation was employed to ensure data validity. The findings reveal that the concept of Nusyúz is often interpreted narrowly as the wife's disobedience, whereas Islamic law recognises that Nusyúz may also apply to husbands who neglect their responsibilities toward their wives. A wife's Nusyúz refers to her disobedience or resistance to her husband, while a husband's Nusyúz occurs when he neglects his material duties, such as providing sustenance, or his immaterial duties, such as showing affection and kindness (mu‘āsyarah bi al-ma'rūf). The academic contribution of this study lies in offering empirical insights into how Nusyúz is understood in Jordan, fostering a more equitable interpretation of marital relations that aligns with the maqāṣid al-sharī‘ah and supports family harmony.